Psychological Reactions in Women with Pregnancy Termination Due to Fetal Anomaly - Turkyilmaz, Gurcan; Atan, Yavuz Selim; Erturk, Emircan; Turkyilmaz, Sebnem (Gynecology Obstetrics & Reproductive Medicine, 2021)
OBJECTIVE: We aimed to determine and compare grief, depression, and post-traumatic stress scores in women who underwent termination of pregnancy due to fetal anomaly in the first vs. second-trimester of pregnancy. STUDY DESIGN: Forty-three women who underwent termination of pregnancy for fetal anomaly were subdivided into two categories in this prospective-cohort study: First-trimester group, which was defined as termination of pregnancy performed <14 weeks of gestation, and Second-trimester termination of pregnancy who underwent termination of pregnancy between 20 and 28 weeks of pregnancy. Eight weeks after the termination of pregnancy, the Beck Depression Inventory, Perinatal Grief Scale-short version, and Impact of Event Scale-Revised were performed with face-to-face interviews. RESULTS: Twenty-four women in the first-trimester group and 19 women in the second-trimester group were enrolled. The mean Beck Depression Inventory score was 7.3±4.2 in the first-trimester group and 11.1±4.6 in the second-trimester group (p=0.033). The mean Perinatal Grief Scale-short scores were 86.3±17.2 and 101.4±29.2 in the first and second-trimester groups, respectively (p=0.014). Impact of Event Scale-Revised scores of the first trimester and second-trimester groups were 22.5±8.6 and 35.3±17.1, respectively (p=0.022). Depression was detected in 29.1% of women in the first-trimester group and 57.8% in the second-trimester group (p=0.023). Perinatal grief was significantly higher in the second-trimester group (45.8% vs. 84.2% p<0.01). Post-traumatic stress was significantly higher in the second-trimester group (41.6% vs. 73.6%, p=0.031). CONCLUSION: Our study indicates that termination of pregnancy for fetal anomaly causes severe psychiatric problems in most women. Depression, grief, and post-traumatic stress are more prominent in women who underwent termination of pregnancy in the second trimester of pregnancy than in the first trimester.